Logistic curve in evaluation of companies on emerging markets - ИвановИлья Федорович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
This paper sheds light upon the logistic curve and one of its possible applications in corporate finance. The logistic curve is a simple and simultaneously powerful mathematical tool that enables the realistic forecast of markets’ growth in developing countries. The model is based upon the assumption that the expansion of sales is limited by the saturation level and is proportionate to the relative number of remaining niches on the market. It seems to be rather realistic because of the competitors’ activities and difficulties of finding and exploiting niches. As a result, the forecasted development of the market consists of three stages: provision of foundation for future development (with little, but increasing growth), extensive growth and, finally, market saturation (with extinguishing growth). Consequently, future dynamics of the market volume can be modeled from any time point onwards by the analysis of the historical development path and the current stage. Such a forecast is crucially important in companies’ evaluation in emerging economies. This application possibility is illustrated by the example of OAO Lebedyansky’s evaluation. This company operates mainly in Russia. Its products are on the markets of fruit and vegetable juice, baby-food, and bottled water. First, the life cycle stage of these markets, as well as their dynamics and further potential of growth are different. Second, the position of the company, its core competences, strategic goals, and marginal profitability on these markets vary either. The logistic curve’s usage makes it possible to take into account the diversity of three business units and, thus, to work out the aggregate financial results and the company’s value more accurately. Therefore, the logistic curve is a very helpful tool of modeling market dynamics in developing countries, which are characterized by extensive and volatile growth.